A Randomized Clinical Trial to Evaluate the Effects of Safinamide on Apathetic Non-demented Patients With Parkinson's Disease - Kulisevsky, Jaime; Martínez-Horta, Saul; Campolongo, Antonia; Pascual-Sedano, Berta; Marín-Lahoz, Juan; Bejr-kasem, Helena; Aracil-Bolaños, Ignacio; Horta-Barba, Andrea; Puig-Davi, Arnau; Pagonabarraga, Javier (Frontiers in Neurology, 2022)
Background: Apathy is highly prevalent and disabling in Parkinson’s disease (PD). Pharmacological options for its management lack sufficient evidence. Objective: We studied the effects of safinamide on apathy in PD. Methods: Prospective, 24-week, two-site, randomized, double-blind, placebo-controlled, parallel-group exploratory study in non-demented PD on stable dopaminergic therapy randomized 1:1 to adjunct safinamide (50mg/day for 2 weeks and 100mg/day for 22 weeks) or placebo. The primary endpoint was mean change from baseline to week 24 on the Apathy Scale (AS) total score. Secondary endpoints included changes in cognition, activities of daily living, motor scores, impression of change, safety and tolerability measures. Results: 30 participants (active treatment=15; placebo=15; 80% showing clinically significant apathetic symptoms according to the AS) were enrolled, and included in the intention-to-treat analysis. Change in AS (ANOVA) showed a trend to significance [p=0.059] mediated by a more marked decrease on AS score with safinamide (-7.5±6.9) than with placebo (-2.8±5.7). Post-hoc analysis (paired t-test) showed a significant positive change in the AS score between 12-week and 24-week [p=0.001] only in the active group. No significant or trend changes were found for any of the secondary outcomes variables. Adverse events were few and only mild in both treatment groups. Conclusions: Safinamide was safe and well tolerated, but failed to provide evidence of improved apathy. The positive trend observed in the post-hoc analyses deserves to be studied in depth in larger studies.